Hands-on guide to webcasting : Internet event and AV production - Mack, Steve (Focal hands-on guide series., 2006)
In ""Hands-On Guide to Webcasting,"" industry experts address the fastest-growing application for streaming media - broadcasting live audio and video on the Internet. Used in all industry verticals from corporate to entertainment, this book provides an end-to-end technical overview of the webcasting process. Providing you with step-by-step instructions from audio/video production, encoding and authoring to delivery and business issues, this guide provides both the depth and breadth necessary for mastery of the subject.